KINERJA PEGAWAI BERDASARKAN PENDELEGASIAN WEWENANG DAN KOMUNIKASI SERTA PERAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - I Gusti Agung Sasih Gayatri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine employee performance based on the delegation of authority and communication as well as the role of job satisfaction as a mediating variable at the Regional Development Bank (BPD) Bali State branch. The sample used in this study were 71 employees. The data used are primary data obtained from questionnaires. The data analysis method uses the Sobel test to analyze the hypothesis with the classical assumption test previously carried out, the results of the study state that partially Delegation of authority has a positive and significant effect on satisfaction, Communication has a positive and significant effect on satisfaction, Satisfaction has a positive and significant effect on performance, Delegation authority has a positive and significant effect on performance through satisfaction, and communication has an effect on performance through satisfaction. Thus, job satisfaction research is able to become a mediating variable.